P294 Resting energy expenditure in women with Crohn's disease: A cross-sectional study. (16th January 2018) - Imperatore, N; Cioffi, I; Sammarco, R; Testa, A; Rispo, A; Marra, M; Contaldo, F; Caporaso, N; Pasanisi, F; Castiglione, F
Abstract: Background: Crohn's disease (CD) is a chronic inflammatory disease that can affect any section of the gastrointestinal tract. Malnutrition is a common sequel in CD patients and many pathogenic mechanisms could be involved such as poor dietary intake, altered energy expenditure, nutrient malabsorption and/or losses. Aim: This cross-sectional study aimed to evaluate the resting energy expenditure (REE) in CD patients. Methods: All consecutive adult CD women were prospectively enrolled, while a group of healthy women, matched for age and weight, served as control group (C). CD women were classified in clinically active disease (CD-A) and clinical remission (CD-R) according to Crohn's disease Activity Index (CDAI) (>150 and <150, respectively). All subjects underwent REE measure by indirect calorimetry with a canopy system, while body composition variables, such as fat free mass (FFM) and fat mass (FM), were assessed by bio-impedance analysis (BIA). Results: Finally, 42 women with CD, 23 with clinically active disease (CD-A; CDAI = 219 ± 53) and 19 in clinical remission (CD-R; CDAI = 83 ± 41) were recruited for the study, while 40 matched-healthy women were enrolled as control group (C). We found that body weight, FFM and phase angle (PA) differed among groups; but age, height and FM did not. Post-hoc analysis revealed that body weight was significantly lower for CD-A in comparison with C (CD-A: 55.7 ± 9.23 kg vs. C: 64.5 ± 6.3 kg; p = 0.02). FFM was reduced in women with CD than C (CD-A: 39.6 ± 4.32 kg and CD-R: 39.5 ± 6.68 kg vs. C: 44.4 ± 4.68 kg; p < 0.01) while PA was lower for CD-A compared with both CD-R and C (CD-A: 5.5 ± 0.6 vs. CD-R: 6.0 ± 0.5 and C: 6.1 ± 0.5; p < 0.001). REE did not differ among groups; nevertheless when it was adjusted for FFM, we observed that REE/FFM increased for both CD-A and CD-R groups compared with C (CD-A: 35.9 ± 4.17 kcal/kg, CD-R: 35.1 ± 4.96 kcal/kg vs. C: 30.2 ± 3.38 kcal/kg; p < 0.01). Conclusions: These preliminary results show that REE, when adjusted for FFM, is increased in women with CD, unrelated to disease activity, compared with healthy subjects and this could negatively affect the energy balance and contribute to weight loss.